Deaf people in Hitler's Europe - Ryan, Donna F.; Schuchman, John S., 1938- (Washington (D.C.) : Gallaudet university press, 2002)
Index
Keywords: Deaf -- Government policy -- Germany; Deaf -- History -- 20th century -- Europe; Deaf -- History -- 20th century -- Germany; Eugenics -- History -- 20th century -- Germany; People with disabilities -- Government policy -- Germany; PBIB:20053.